A simplified model for a diesel spray. (15th June 2018) - Marčič, Simon; Marčič, Milan; Wensing, Michael; Vogel, Thomas; Praunseis, Zdravko
Abstract: This paper describes a computer simulation and measurements of the liquid phase of Diesel spray formation. The spray is divided into small elementary volumes in which the amounts of liquid and gaseous fuel, air, mean, maximum and minimum fuel droplet diameter are calculated, as well as their number. The total air–fuel and air–fuel vapour ratios are calculated for each elementary volume. The mathematical model of the Diesel spray is based on continuity and momentum equations in Eulerian-Lagrangian formulation. The measurements of the sprays were carried out in the combustion chamber at the LTT, which is equipped with a high pressure 250 MPa fuel injection system. During the experiments, ambient pressure varied from 3 MPa to 7 MPa, temperature from 673 K to 973 K, injection pressure from 40 MPa to 200 MPa and nozzle temperature from 243 K to 363 K. The injection quantity was 13.5 mm 3 per cycle in all cases. The combustion chamber was filled with pure nitrogen instead of air. Thermodynamic properties of nitrogen are similar to those of air. That way, self-ignition was prevented. We measured only the liquid phase of the fuel in the spray, and to this end, Mie scattering measuring technique was applied. The comparison between the simulated and actual liquid spray penetration depth and spray cone angle showed good matching.